U-shaped wage curve and the Internet: The Colombian case - Martin, Diego A. (Estudios de Economía, 2018)
While there is a broad consensus in the literature that there is a positive correlation between Internet usage and labor income in the richest countries, this link has not been proven in the developing world. This paper uses propensity score matching techniques and household survey data to estimate the effect of the Internet on wages in Colombia, a country that has experienced a relatively rapid diffusion of information and communications technology in recent years. The empirical results confirm that there is a positive and statistically significant relationship between Internet use and income in this country. Consistent with evidence gathered on developed countries in previous studies, the empirical results also suggest that workers in the middle of the skill distribution receive the lowest wage premium for using the Internet. However, contrary to most evidence from developed countries, low skilled workers in Colombia enjoy the highest wage premium from Internet use, which illustrates the potential for new technologies to address inequality gaps between occupations.